The Idea of a University: Rethinking the Malaysian Context - Chang Da Wan; Morshidi Sirat; Dzulkifli Abdul Razak (Humanities, 2015)
This article explores the idea of a university with a specific focus in the Malaysian context. We begin the article guided by these questions—“What is a university?” and “What are universities for?”—in examining the historical and conceptual development of universities. This is followed by asking a more specific question—“What are Malaysian universities for?”—in which we discussed the overarching roles of public and private universities in this developing country. Having examined the roles of public and private universities, and taken into context the complexity and challenges surrounding these important societal institutions, we discuss two “experimental” initiatives in Malaysia: the APEX University (Accelerated Program for Excellence) focusing on sustainability and the “humanversity”. On the one hand, these initiatives are intended to prepare and transform Malaysian universities to address not only the needs of society today, but critically, of tomorrow. On the other hand, they have implications and contributions to frame our thinking about the future ideas of a university not only in Malaysia, but regionally and globally.